Impact of coffee crop renewal program on small producers in department cundinamarca (colombia) (2012)
The modernization of crops through renewal is a vital option for the restoration of the productivity and competitiveness of the coffee crop. The Federación Nacional de Cafeteros (National Federation of Coffee) is banking on a strategy that promotes renewal by providing resources to stimulate growers. As a result of the implementation of the program, it is hoped that it will reverse the aging process of coffee crops, consolidate a productive and competitive market, provide appropriate ages and densities and promote the use of coffee rust resistant varieties. Similarly, it is expected that small producers, who constitute the majority of farmers and who presumably suffer major limitations to independent renewal, will be the main beneficiaries.